Assessment of Sound Pollution and Control Initiatives in Growing Suburb of Jhapa, Koshi Province of Nepal - Neupane, Nisha; Chauhan, Raju (Journal of Environment Sciences, 2024)
This study presents an assessment of noise pollution in Gauradaha Municipality, Nepal, focusing on sound level measurements and evaluation of noise control initiatives across five categorical areas: commercial, industrial, quiet, rural, and urban residential zones. Using a systematic sampling approach, three sites per category were selected across nine wards, with sound level measurements conducted using a Sound Level Meter at 10-second intervals for 10 minutes, five times between 6 am and 9 pm. Questionnaire surveys were also administered to assess community perceptions and existing noise control measures. Results indicate widespread noise pollution exceeding both national and WHO standards, with an overall equivalent sound level of 65.19 dBA. Industrial areas exhibited the highest levels (90.78 dBA), while rural areas showed the lowest (47.34 dBA). Control measures predominantly included no horn zone declarations and physical barriers such as cemented structures and bamboo barriers. However, effectiveness varied across areas, suggesting a need for enhanced enforcement and community awareness. This study underscores the urgent need for targeted interventions to mitigate noise pollution, recommending strengthened enforcement of regulations, increased community awareness, and innovative solutions tailored to specific sources of noise pollution in each area.